The Minority Report: Targeting the Rare Oncogenes in NSCLC - McCoach, Caroline E. (Curr Treat Options Oncol, 2014)
Lung cancer is still responsible for the highest number of cancer deaths worldwide. Despite this fact, significant progress has been made in the treatment of non-small cell lung cancer (NSCLC). Specifically, efforts to identify and treat genetic alterations (gene mutations, gene fusions, gene amplification events, etc.) that result in oncogenic drivers are now standard of care (EGFR and ALK) or an intense area of research. The most prevalent oncogenic drivers have likely already been identified; thus, there is now a focus on subgroups of tumors with less common genetic alterations. Interestingly, as we explore these less common mutations, we are discovering that many occur across other tumor types (i.e., non-lung cancer), further justifying their study. Furthermore, many studies have demonstrated that by searching broadly for multiple genetic alterations in large subsets of patients they are able to identify potentially targetable alterations in the majority of patients. Although individually, the rare oncogenic drivers subgroups may seem to occur too infrequently to justify their exploration, the fact that the majority of patients with NSCLC harbor a potentially actionable driver mutation within their tumors and the fact that different types of cancers often have the same oncogenic driver justifies this approach.